2005
DOI: 10.1371/journal.pbio.0030045
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Death in an Organism That Reproduces by Morphologically Symmetric Division

Abstract: In macroscopic organisms, aging is often obvious; in single-celled organisms, where there is the greatest potential to identify the molecular mechanisms involved, identifying and quantifying aging is harder. The primary results in this area have come from organisms that share the traits of a visibly asymmetric division and an identifiable juvenile phase. As reproductive aging must require a differential distribution of aged and young components between parent and offspring, it has been postulated that organism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
727
4
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 658 publications
(773 citation statements)
references
References 27 publications
36
727
4
6
Order By: Relevance
“…We applied our procedure to the Escherichia coli data of Stewart et al (2005). The biological issue addressed is aging in single cell organisms.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We applied our procedure to the Escherichia coli data of Stewart et al (2005). The biological issue addressed is aging in single cell organisms.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, studies of aging in single cell organisms by Stewart et al (2005) suggested that cell division may not be symmetric. An asymmetric BAR model was therefore proposed by Guyon (2007), where the two sets of parameters corresponding to sister cells are allowed to be different.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations